Improving letter recognition skills through multisensory methods in Grade 1 Students at UPTD SD Inprens Sikumana 3, Kupang City - Dinengsih Liliani Panab; Markus Sampe; Maxsel Koro (ARKA INSTITUTE, 2026)
The multisensory method is a learning approach that has been proven effective for helping students with early reading difficulties, especially in the letter recognition stage. This approach integrates various senses simultaneously, so that students not only see and hear letters but also touch and engage in physical activities related to the shape and sound of letters, making the learning process more concrete, interesting, and aligned with students’ learning styles. This study aims to improve the early reading skills of first-grade students at UPTD SDI Sikumana 3 in Kupang City by applying the multisensory method through Classroom Action Research (CAR) conducted in two cycles, focusing on the aspects of the learning process and outcomes. The results show a significant increase in students’ reading skills, from 15% of students who achieved mastery at the beginning to 90% at the end of cycle II. However, one student still needed additional help, so differentiated learning strategies were applied. Overall, the application of the multisensory method has been proven to improve the effectiveness of early reading instruction, but it still requires continuous evaluation and adjustment for optimal results.